Andrographis paniculata improves growth and non-specific immunity of shrimp Litopenaeus vannamei, and protects it from Vibrio alginolyticus by reducing oxidative stress and apoptosis. (February 2023) - Yin, Xiaoli; Zhuang, Xueqi; Liao, Meiqiu; Cui, Qiqian; Yan, Chunxia; Huang, Jiayi; Jiang, Zixiang; Huang, Lin; Luo, Weitao; Liu, Yuan; Wang, Weina
Abstract: Andrographis paniculata (AP) is a traditional medicinal plant with many pharmacological activities, including anti-inflammatory, antimicrobial, immunity stimulation and so on. Several studies have reported that AP plays a strong role in promoting the immune system of aquatic animals to resist several pathogens. In the present study, we investigate the effects of a diet containing AP on the immune responses, growth, and the resistance to Vibrio alginolyticus (V. alginolyticus) in Litopenaeus vannamei (L. vannamei) . Four diets were formulated by adding AP at the dosage of 0% (Control), 0.25%, 0.5%, and 1% in the basal diet, respectively. Each diet was randomly fed to one group with three replicates of shrimps in a 28-day feeding trial. The results showed that dietary AP improved the growth performance and non-specific immune function of shrimps. To investigate the effect of AP on disease resistance o f L. vannamei, shrimps fed with diet containing AP were challenged with V. alginolyticus. Compared with the control group, the shrimps fed diet containing AP showed significantly higher survival. Furthermore, the hepatopancreas injury in the shrimp fed with AP was less than control group at 6 h after V. alginolyticus infection. However, no difference was observed in the degree of hepatopancreas injury between AP groups and control group at 12 h and 24 h after V. alginolyticus infection. Based on this result, the samples at 6 h after V. alginolyticus infection was selected for subsequent detection. Reactive oxygen species (ROS) accumulation in hemocytes and O2 − production in hepatopancreas caused by V. alginolyticus infection was significantly reduced after feeding a diet containing 0.25% and 0.5% AP ( p  < 0.05). In addition, we found that feeding AP significantly up-regulated the expression of pro-apoptotic genes (Bax, Caspase 3, p53) and down-regulated the expression of anti-apoptotic genes (Bcl-2) in hepatopancreas after V. alginolyticus infection. In conclusion, AP promote the growth and immunity of L. vannamei, and protects shrimps against V. alginolyticus by regulating the oxidative damage and apoptosis. These results provide useful information regarding the effects of AP extracts as a shrimp feed additive for sustainable shrimp culture. Highlights: Dietary AP improves the growth performance of Litopenaeus vannamei after 28 days feeding trial. AP water extract can promote phagocytic rate and phagocytic index of hemocytes in L. vannamei. AP can reduce the accumulation of ROS and apoptosis in L. vannamei and protect shrimp from V. alginolyticus infection.